HUBUNGAN KEMAMPUAN BERPIKIR KRITIS DENGAN KECERDASAN INTERPERSONAL SISWA SEKOLAH DASAR - Kania, Anggun; Sa’diah , Tia Latifatu; Anggraeni, Sri Wulan (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
A person's success in various aspects of life depends on their ability to think critically and their interpersonal intelligence. Interpersonal intelligence allows someone to interact and communicate effectively with others, build strong relationships, understand and manage their emotions well, and make well-informed decisions based on the information they analyze. The combination of these two skills not only enhances a person's professional performance but also improves their ability to lead, collaborate, and adapt to changing and complex environments. This study aims to determine the relationship between critical thinking skills and interpersonal intelligence of fourth-grade students at SD Gugus II, East Karawang District. Field observations show that students are able to analyze and complete individual tasks well, but lack communication and discussion skills when working on group tasks. This quantitative research used a sample of 268 students with data collection techniques in the form of critical thinking ability tests and interpersonal intelligence questionnaires. The data analysis was conducted using Pearson correlation. The research results show a significant correlation between critical thinking skills and interpersonal intelligence with a Pearson correlation value of 0.359 and a significance of 0.000. These findings indicate that improving critical thinking skills can help enhance students' interpersonal intelligence.